Humoral response in Leishmaniasis - Conde, Luciana; Maciel, Gabriela; de Assis, Gustavo Meira; Freire-de-Lima, Leonardo; Nico, Dirlei; Vale, André; Freire-de-Lima, Célio Geraldo; Morrot, Alexandre (Frontiers in Cellular and Infection Microbiology, 2022)
Leishmaniasis presents different types of clinical manifestations that can be divided into cutaneous leishmaniasis and visceral leishmaniasis. The host’s immune system, associated with genetic and nutritional factors, is strongly involved in the evolution of the disease or parasite escape. Humoral immunity is characterized by the production of antibodies capable of promoting neutralization, opsonization, and activation of the complement system. In this scenario, B lymphocytes produce antibodies that play an important role in Leishmania infection although neglected for a long time. Thus, relevant aspects in the establishment of Leishmania infection will be addressed, highlighting the importance of humoral immunity during the entire process of Leishmania infection.